Optimising information systems in business - Ahmad Dahlan, Abdul Rahman; Yahaya, Muhammad Ezzat Emir; Abdul Rahman, Muhamad Helmi; Ishak, Ahmad Sobri; Rosli, Muhammad Azli (International Journal of Engineering Research and Management (IJERM), 2016)
The world of business is getting bigger from time to time. In beginning of business, it was started by barter system, then change to currency system which requires an exchange between goods and money by face to face. However, internet has been introduced and used by all people in this world. The advances in information and communication technologies (ICT) affect the social with negative and positive thought. In this paper, we will discuss about the positive thought of information system (IS) in business. Nowadays, most of organizations are using IS to create an easy way to expand their businesses while giving maximum benefits to customers. Al-Ikhsan Cooperation is selected as an organization to study about how information system help an organization to have a better performance of the operation in the world of business. This project will give a lot benefit to both of the customers and sellers. Literature review, BMC (Business Model Canvas) and 4 Lenses of Innovation tools are used as methodology for this paper. By this project, the operation of the business will become smooth in all aspects, including supply chain and customer relationship management.